2016
DOI: 10.1007/s10461-016-1412-z
|View full text |Cite|
|
Sign up to set email alerts
|

Consistent Condom Use by Female Sex Workers in Kolkata, India: Testing Theories of Economic Insecurity, Behavior Change, Life Course Vulnerability and Empowerment

Abstract: Consistent condom use (CCU) is the primary HIV/STI prevention option available to sex workers globally but may be undermined by economic insecurity, life-course vulnerabilities, behavioral factors, disempowerment, or lack of effective interventions. This study examines predictors of CCU in a random household survey of brothel-based female sex workers (n = 200) in two neighborhoods served by Durbar (the Sonagachi Project) in Kolkata, India. Multivariate logistic regression analyses indicated that CCU was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 34 publications
3
27
0
2
Order By: Relevance
“…As a result, CCU remains a central goal of Durbar’s programming because condoms protect FSW from other sexually transmitted infections (STIs) and are commonly used as a form of contraception. In a previous analysis with the study population in Kolkata (13), we found that nearly half of FSW reported symptoms of an STI that required treatment within the previous 12 months. Additionally, 92% used condoms as a form of contraception, whereas only 16% used oral contraceptive pills.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…As a result, CCU remains a central goal of Durbar’s programming because condoms protect FSW from other sexually transmitted infections (STIs) and are commonly used as a form of contraception. In a previous analysis with the study population in Kolkata (13), we found that nearly half of FSW reported symptoms of an STI that required treatment within the previous 12 months. Additionally, 92% used condoms as a form of contraception, whereas only 16% used oral contraceptive pills.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, 92% used condoms as a form of contraception, whereas only 16% used oral contraceptive pills. Less than 2% used any other form of hormonal or long-acting reversible contraceptives (13). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations